Correlation of the Stature to Forearm Length in the Young Adults of Western Indian Population. (Medico Legal Update, 2021)
Introduction: Forensic anthropometry dealing with the application of anthropometric measurements ofhuman individual for the purposes of the identification of human remains. Inter and intra population variationscan be observed in relation to anthropometric measurements due to factors such as genetic makeup, age,gender and ethnicity and help in the identification of individual in criminal investigations.Method: This is cross sectional study using young adult students of age group 17 to 24 years. Participantsenrolled after due consent and stature(S) and forearm length (FAL) were measured using standardanthropometric techniques. SPSS statistical package used to calculate Pearson’s coefficients of correlationand regression equations between stature and the anthropometric variables.Results: There were total 255 participants including 54 (21.18%) males and 201 (78.82%) females.Regression equation for estimation of stature from right forearm length is S = 1.4111 Rt FAL+ 126.72, andfrom left forearm length is S = 1.3774 Lt FAL+ 128.39. There were strong positive correlations betweenheight and forearm lengths in all regressions (r >0.9; p < 0.0001).Conclusions: The proposed regression equations based on forearm length presented here will simplify thetask of stature estimation for adults in clinical forensic medicine or as aids to the identification in criminalinvestigation in endogenous population. The left forearm length is more accurate in estimating the stature ofyoung adults of western Indian population.